Factors affecting profit growth in insurance companies listed on the Indonesia Stock Exchange in 2017-2019 - Ganefo Sudirman; Lukman Anthoni (Journal of Economics and Business Letters, 2021)
This study aims to examine the factors that affect the company's profit growth. In this study, the factors that influence profit growth are premium income, claim payments and risk based capital. The data used in this study is the annual report of insurance companies listed on the Indonesia Stock Exchange in the 2017-2019 period. This study uses quantitative methods. This study uses multiple linear regression analysis tools. The implications of the research are expected to make a positive contribution to all parties. As a consideration for insurance companies in observing factors that have a direct influence, especially those that are quite significant on the company's profit growth. This research is also expected to be useful for investors and potential investors in seeing opportunities to increase the value of shares held in insurance companies listed on the IDX. The regulator can also assess and supervise the factors that affect profit growth in insurance companies so that problems arising from insurance companies that fail to pay claims do not recur in the future. Insurance companies are expected to present appropriate financial reports so that the information obtained Therefore, the quality of the financial statements must also be considered so that the information obtained can be accounted for. The results of previous studies show that premium income, claim payments and risk based capital significantly affect the profit growth of insurance companies